Fabrication of Surface Embedded Silver Cellulose-based Flexible Transparent Electrodes by Self-Assembly - Wentao Zhang; Tianhao Wang; Ying Zhu; Yanan Gao; Lin Liu; Mengling Li; Liping Zhang (BioResources, 2024)
Developing eco-friendly, degradable, and flexible electronic devices using renewable cellulose, such as waste agricultural straw, is increasingly vital. This approach tackles the growing issue of nondegradable electronic waste. In this study, flexible transparent electrodes (FTEs) were created using cellulose from waste corn straw, embedding silver nanowires (AgNWs) networks within the surface layer. This method is suitable for reel-to-reel processing. These sustainable FTEs had high transparency and conductivity, with a film resistance of 45.4 Ω/sq and light transmittance of 86.2% at 550 nm. The "dissolution–regeneration" self-assembly process harnesses cellulose's hydrogen bond network to stabilize the AgNWs network, providing the FTEs with excellent electromechanical stability. Resistance changes were less than 3% during bending, folding, and 1,000-time cyclic bending tests. Furthermore, these electrodes showed remarkable environmental stability, with only a 2.5% resistance increase after 16 days at room temperature. This research demonstrates a new application for agricultural straw cellulose in flexible electronics, offering a sustainable alternative in electronic materials.